Plan de marketing para aero world travel agency & tour operator, ubicada en la ciudad de Quito provincia de Pichincha - Jami Arequipa, Jessica Lorena (2016)
The purpose of the research is to design a marketing plan for AERO WORLD TRAVEL AGENCY & TOUR OPERATOR, being thus a fundamental tool that will allow to increase its sales and thereby achieve the current position in the market the Quito city. Three chapters were made for this purpose. Within the first chapter are all the legal aspects that underpin the investigation, we will also cover everything related to the area of study from its macro, meso and micro location, thus we will obtain a situational diagnosis of the site, taking information both social, economic, tourism and environmental continued the SWOT analysis where they established strategies which will allow the positioning of the company. In the second chapter, the market study was developed, which was applied to 153 surveys in order to obtain information of the elements that participate in a market, the same one that is focused to extract the requirements of the clients what the market study helped to a correct decision making around the positioning of the company. The third chapter develops the proposal of the Marketing Plan where the analysis of the SWOT matrix, the market study; followed by the development of the logical framework methodology establishing four programs based on tourism, economic, social and environmental with their respective subprograms in order to improve activities into the company.